Director's Cut - Analysis of VR Film Cuts for Interactive Storytelling - Fearghail, Colm O; Ozcinar, Cagri; Knorr, Sebastian; Smolic, Aljosa (2018 International Conference on 3D Immersion (IC3D), 2018)
The usage of film cuts, or transitions, is a powerful technique in interactive storytelling to express the film story by leading the viewers attention. To explore how existing transition techniques are currently being used by professional 360° filmmakers, this paper investigates the impact of transitions and additional graphical elements from a storytelling perspective. We base this on the recently published Director's Cut dataset [1] which contains professional 360° films with the directors' intending viewing direction (i.e., director's cut) and test subjects' scan-paths. Our objective is to examine widely used transition techniques in professional 360° film, and with our finding guide filmmakers in the storytelling and editing process. To the authors knowledge, this is the first study to analyze professionally prepared VR film cuts concerning the distance of viewers' scan-paths and director's cut. We observed that the intended viewing direction is required for the viewer to understand the story best and not miss the director's plot points. The transition is a point where the viewers are presented with a new scene and are required to orientate themselves within it. Thus if there is a considerable distance mismatch between the intended and actual viewing, the viewer is not in the best position to understand the scene properly. Our results show that the use of simple graphics can serve as a reference for viewers as the transition happens and they are presented with a new immersive environment.